2016
DOI: 10.17925/eor.2016.10.02.80
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconus Screening in Primary Eye Care – A General Overview

Abstract: Keratoconus early detection (screening) and diagnosis requires an in-deep corneal analysis with different techniques; slip lamp assessment, corneal topography and corneal tomography are the most commonly accepted to detect clinical signs and assess anterior and posterior corneal surface and global corneal pachymetry. However, keratoconus early detection and definitive diagnosis are two different clinical procedures that require a different approach and goals. The aim of this review is to provide some general i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…50 Upskilling programmes are usually mandated across healthcare professions for specific purposes such as when the scope of practice is increased or for special needs such as the case of KC. 51,52 Optometrists in this study have shown an interest in enrolling in such programmes. They are mostly young adults and therefore are likely to embrace the challenges with their knowledge and skills of KC patient care given their improvement.…”
Section: Optometrists (%)mentioning
confidence: 88%
“…50 Upskilling programmes are usually mandated across healthcare professions for specific purposes such as when the scope of practice is increased or for special needs such as the case of KC. 51,52 Optometrists in this study have shown an interest in enrolling in such programmes. They are mostly young adults and therefore are likely to embrace the challenges with their knowledge and skills of KC patient care given their improvement.…”
Section: Optometrists (%)mentioning
confidence: 88%
“…The data available in literature does not prove to be definitive in diagnosing Keratoconus as there is a considerable overlap between normal corneas and Forme Fruste Keratoconus 16,17 . In this study, we compared the accuracy of CBI in Keratoconus screening by calculating their sensitivity and specificity against TBI from the collected data and their positive and negative predictive value.…”
Section: Discussionmentioning
confidence: 97%
“…Corneal tomography is a technique that allows for three-dimensional visualization of the anterior and posterior corneal surfaces, along with assessment of corneal thickness ( Figure 1 ). 7 , 8 It has emerged as a promising screening tool in the identification of candidates for early corneal collagen cross-linking to prevent disease progression and more invasive surgical interventions. A recent study by Kong et al reported that while nearly 50% of patients receive corneal topography at their initial visit, the use of corneal tomography at a patient’s first visit has increased significantly since 2015, with pediatric patients more likely to receive corneal tomography compared to adult patients.…”
Section: Screening For Keratoconusmentioning
confidence: 99%